"Just like Jail": Trauma Experiences of Older Homeless Men. Issue 3 (2nd April 2020) - Pope, Natalie D.; Buchino, Susan; Ascienzo, Sarah
ABSTRACT: People experiencing homelessness often have a history of trauma, and losing one's home is a traumatic event. The trauma of living in emergency shelters and on the streets uniquely impacts older adults, whose experiences of homelessness increase the likelihood of multiple health conditions and premature aging. This paper includes data from 18 men, aged 50 and older, who had experienced multiple instances of homelessness, as part of a larger study to understand the return path to homelessness from permanent housing. When participants spoke with us about their failure to be in housing, their inability to free themselves from reoccurring homelessness could not be discussed without talking about their trauma. Participants spoke of trauma in early life, perhaps precipitating homelessness, as well as traumatic experiences while homeless. The men discussed feeling imprisoned by the systemic issues around homelessness, facing mistreatment by service providers, and being exposed to external threats in their lives on the streets, including violence. Findings from this study lend themselves to the explicit need for trauma-informed care and supportive services that are sensitive to the urgency of homelessness as it is experienced by men in late life.